DPPH SCAVENGING ACTIVITY OF DIOSCOREA BATATAS TUBERS - R.SANDIYA,; M.MUNNIAPPAN, (International Journal of Pharma and Bio Sciences, 2015)
Reactive oxygen species [ROS] cause oxidative damage to the tissues and protection from such damages are provided by endogenous and exogenous antioxidants. Plant based antioxidants are preferred due to the multiple mechanisms of actions and of the phytochemicals present in them. Different doses of Alcoholic Tuber extract of Dioscorea batatas were tested individually in equal proportion of each dose for DPPH scavenging activity and reducing power. The results indicate that the highestdoses of Alcoholic Tuber extract of Dioscorea batatas (100 µg) has better DPPH scavenging action and reducing power compared to the lower doses of the plant extract indicating effect of phytochemicals present in the extract indicating its antioxidant potential.